A Comparative Study of Growth Patterns in Crested Langurs and Vervet Monkeys. (21st February 2011) - Bolter, Debra R.
Abstract : The physical growth patterns of crested langurs and vervet monkeys are investigated for several unilinear dimensions. Long bone lengths, trunk height, foot length, epiphyseal fusion of the long bones and the pelvis, and cranial capacity are compared through six dental growth stages in male Trachypithecus cristatus (crested langurs) and Cercopithecus aethiops (vervet monkeys). Results show that the body elements of crested langurs mature differently than those of vervets. In some dimensions, langurs and vervets grow comparably, in others vervets attain adult values in advance of crested langurs, and in one feature the langurs are accelerated. Several factors may explain this difference, including phylogeny, diet, ecology, and locomotion. This study proposes that locomotor requirements affect differences in somatic growth between the species.